Analisis Pengaruh Biaya Produksi dan Biaya Penjualan Untuk Meningkatkan Profitabilitas Pada PT. Alpen Food Industry - Yusrina Hasibuan; Yenni Samri Juliati; Nuwani N (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to determine the effect of production costs and selling costs on profitability at PT. Alpine Food Industry. This research uses quantitative methods. The population and sample in this study are the quarterly financial reports of PT. Alpen Food Industry 2014-2021 period. The sampling technique is using purposive sampling. Data collection techniques with documentation using data from the quarterly financial reports of PT. Alpen Food Industry 2014-2021 period. Data were analyzed using multiple linear regression analysis method. The results of this study indicate that Production Costs have a positive and significant effect on Profitability, with the tcount value for the Production Costs variable (5.004) greater than ttable (2.045) and a sig value of 0.007 <0.05. Selling Costs have a positive and significant effect on Profitability, with the tcount value for the Selling Costs variable (6.950) greater than ttable (2.045) and a sig value of 0.005 <0.05. Based on the F test of Production Costs and Selling Costs, they have a simultaneous and significant effect on Profitability, with a Fcount value of (5.406) greater than Ftable (4.18) and a sig value of 0.015 <0.05. The test results for the coefficient of determination show that the R Square value is 0.686. This shows that the independent variables, namely Production Costs and Sales Costs, are able to explain the dependent variable, namely Profitability of 68.6% while the remaining 31.4% is explained by other variables outside the regression model.